FEATURES OF OTOGENIC INTRACRANIAL COMPLICATIONS AT THE PRESENT STAGE - A. A. Krivopalov; Yu. K. Yanov; S. V. Astashchenko; A. Yu. Shcherbuk; S. A. Artyushkin; S. G. Vakhrushev; I. S. Piskunov; V. S. Piskunov; N. A. Tuzikov (Вестник хирургии имени И.И. Грекова, 2015)
A retrospective analysis of treatment was made in 127 adult patients with acute and chronic otitis media complicated by suppurative-inflammatory pathology of the brain. Purulent meningitis was revealed in 52 (40,9%) of hospitalized patients. Meningoencephalitis was often diagnosed in the cases of acute otitis media (15,4%) and in cases of chronic otitis (22,7%). The otogenic brain abscess was detected in 13,5% of otitis media cases and it was noted to be twice frequent (33,3%) in cases of purulent otitis media. The patients 124 (97,6%) have been operated. An extended mastoidotomy and antromastoidotomy were performed in the acute purulent otitis media. An extended radical operation on the ear was applied in case of chronic otitis media. Performance of craniotomy and complete removal of the abscess using modern systems of neuronavigation showed a higher clinical efficacy as compared with transtemporal approach during sanitizing intervention on the ear including the opening and abscess drainage in surgery of otogenic abscesses of the brain.